2021
DOI: 10.3389/fphys.2020.609935
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral Hemodynamic and Neurotrophic Factor Responses Are Dependent on the Type of Exercise

Abstract: This study examined acute cerebral hemodynamic and circulating neurotrophic factor responses to moderate intensity continuous exercise (MICT), guideline-based high intensity interval exercise (HIIT), and sprint interval exercise (SIT). We hypothesized that the pattern of middle cerebral artery velocity (MCAv) response would differ between interval and continuous exercise, with SIT inducing the smallest increase from rest, while increases in neurotrophic factors would be intensity-dependent. In a randomized cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 85 publications
(114 reference statements)
2
29
0
1
Order By: Relevance
“…Recently, a notable study compared cerebral hemodynamics and circulating neurotrophic factor responses to three different types of exercise regimens in healthy adults. They found an interesting phenomenon, compared with the traditional continuous exercise (65% VO2peak, lasting 30 min) and HIIT (85% HRmax, 4 × 4 min), and ultra-high-intensity intermittent exercise with 200% maximum aerobic capacity (4 × 30 s) could maximize the increase of VEGF and BDNF ( Weaver et al, 2020 ). More importantly, the lactate produced by this training paradigm showed the most significant increase, suggesting the potential connection of lactate with these factors.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a notable study compared cerebral hemodynamics and circulating neurotrophic factor responses to three different types of exercise regimens in healthy adults. They found an interesting phenomenon, compared with the traditional continuous exercise (65% VO2peak, lasting 30 min) and HIIT (85% HRmax, 4 × 4 min), and ultra-high-intensity intermittent exercise with 200% maximum aerobic capacity (4 × 30 s) could maximize the increase of VEGF and BDNF ( Weaver et al, 2020 ). More importantly, the lactate produced by this training paradigm showed the most significant increase, suggesting the potential connection of lactate with these factors.…”
Section: Main Textmentioning
confidence: 99%
“…Another study reported that compared with resting control, subjects after acute sprint interval exercise have significantly higher levels of peripheral blood lactate and are associated with higher levels of BDNF, IGF-1, and VEGF, which is also related to better performance in cognitive function tests ( Kujach et al, 2019 ). A recent study also highlighted the potential link between lactate and neuroplasticity ( Weaver et al, 2020 ).…”
Section: Main Textmentioning
confidence: 99%
“…Previous studies measuring MCAv during HIIE have also reported this “rebounding” effect. (11, 12, 34) MCAv “rebounding” during light intensity intervals could be partially explained by P ET CO 2 as they were moderately correlated. MCAv also closely followed the pattern of P ET CO 2, with both measures decreasing during high intensity (hyperventilation) and increasing during recovery.…”
Section: Discussionmentioning
confidence: 92%
“…Our results are supported by previous research performing short sprint interval training in healthy adults that also found no reduction in MCAv below BL resting MCAv. (12) However, the prior study performed 30-second sprint intervals at 200% watt maximum with longer 4.5-minute recovery intervals. Therefore, our study contributes to the existing literature showing no reduction in MCAv below BL during an acute 10-minute bout of short interval HIIE with alternating 1-minute high intensity and low intensity intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation